2022
DOI: 10.21608/jabps.2022.136094.1157
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Assessment of Celecoxib Floating Beads in Capsule using 2^3 Full Factorial Design

Abstract: Floating beads have been formed to create a prolonged drug release in the stomach and to reduce the number of frequencies, thereby overcoming its side effects. The current study is concerned with the design and evaluation of stomach-specific oil embedded floating beads of celecoxib in a capsule. Hard gelatin capsules (size 1) were filled with celecoxib oil entrapped beads. A 2³ factorial design was used to investigate the effects of different weight masses of HPMC K4M, Sodium alginate, and maize starch on drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The TEL-loaded oil-entrapped floating alginate beads were formulated by emulsion-gelation method using calcium chloride (CaCl 2 ) as a cross-linking agent [ 21 ]. In this method, a sodium alginate solution with various concentrations was prepared by dissolving an accurate amount of sodium alginate in distilled water at room temperature using a magnetic stirrer (Remi Motor, Mumbai, India).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TEL-loaded oil-entrapped floating alginate beads were formulated by emulsion-gelation method using calcium chloride (CaCl 2 ) as a cross-linking agent [ 21 ]. In this method, a sodium alginate solution with various concentrations was prepared by dissolving an accurate amount of sodium alginate in distilled water at room temperature using a magnetic stirrer (Remi Motor, Mumbai, India).…”
Section: Methodsmentioning
confidence: 99%
“…An accurate amount of TEL (100 mg) was dispersed in sesame oil and mixed with the aqueous solution of sodium alginate in the presence of Tween 80 (0.5%) as an emulsifier by high-shear mixing for 20 min at 2000 rpm using a magnetic stirrer to form an O/W emulsion. The emulsion mixture was extruded into a calcium-chloride solution under mild stirring using a syringe G 21 needle [ 21 ]. The gel beads were allowed to stand in the solution for 15 min to complete the curing reaction and to produce rigid beads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to the longer time consumed by high in contrast with previously reported data in literature as it was reported that increasing oil concentration from 15 to 20% w/v would retard drug release (negative effect) because increasing oil would form an additional diffusional barrier for the drug release resulting in slow release of drug from beads 9,39 . Moreover, the drug might stay saturated and distributed in the oil resulting in a drug-oil distributed network 46 .…”
Section: Analysis Of Factorial Design Effect Of Variables On Mean Dia...mentioning
confidence: 99%